Joan of Arc : The Image of Female Heroism - Warner, Marina (UK Oxford University Press, 2016)
A fascinating study of the symbolism of Joan of Arc in her own time and ever since in literature, politics, on the stage, and on screen.
Include Index and Bibliography
Keywords: France -- Christian saints -- Christian women saints